Mechanisms of human genetic disease - Maher, Eamonn (Henry Stewart Talks, 2021)
Mechanisms of human genetic disorders, Loss of function effects, Dominant negative mechanisms, Increased gene dosage, Gain of function effects, Proteins toxicity, Abnormal gene expression and regulation